Intramedullary spinal cord abscess. Issue 3 (March 1992) - Carús, M E Miranda; Anciones, B; Castro, A; Lara, M; Isla, A
Abstract : We report a patient with a chronic intramedullary spinal cord abscess who suffered an episode of acute meningitis due to rupture of the abscess into the subarachnoid space.